Sistem Pendukung Keputusan Pemberian Kredit Koperasi Simpan Pinjam Menggunakan Metode MARCOS dan Rank Order Centroid - Badiwibowo Atim, Sandi; Wibawa, Yohanes Eka (PT. SNN MEDIA TECH PRESS, 2024)
Savings and loan cooperatives are an economic organization that aims to provide financial support to their members through savings and lending mechanisms. The problem experienced by XYZ savings and loan cooperatives is that no creditworthiness assessment system exists in the cooperative. The credit granting process is carried out by conducting a survey from survey officers through forms, submission requirements, and member business taxation formats to conduct committee meetings. This study aims to apply a decision model in lending to savings and loan cooperative customers by applying the MARCOS method with the centroid rank order weighting method so that the results of applying this method become a decision recommendation for the cooperative in determining credit. The ranking results above show the recommendation for providing the first credit to customer 5 with a final value of 0.89323 getting rank 1, then customer 6 with a final value of 0.82269 getting rank 2, and customer 2 with a final value of 0.78972 getting rank 3.